2020
DOI: 10.3233/jad-200463
|View full text |Cite
|
Sign up to set email alerts
|

Development and Validation of a High Sensitivity Assay for Measuring p217 + tau in Cerebrospinal Fluid

Abstract: Background: Early and accurate detection and staging is critical to managing Alzheimer’s disease (AD) and supporting clinical trials. Cerebrospinal fluid (CSF) biomarkers for amyloid-β peptides, tau species, and various neurodegenerative and inflammatory analytes are leading the way in this regard, yet there is room for improved sensitivity and specificity. In particular tau is known to be present in many different fragments, conformations, and post-translationally modified forms. While the exact tau species t… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

0
33
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
6
1

Relationship

3
4

Authors

Journals

citations
Cited by 22 publications
(33 citation statements)
references
References 29 publications
0
33
0
Order By: Relevance
“…The assay relies on the high affinity and specificity of the PT3 mAb, which recognizes tau phosphorylated at threonine residues 212 and 217 22 . Phosphorylation of amino acid 217 is the minimally required epitope, yet phosphorylation of amino acid 212 enhances binding, and thus the recognition is termed “p217+tau.” As described for the CSF p217+tau assay, measurement of species containing both p212 and p217 may yield additional diagnostic relevance than measurement of just one of these residues 19 . Indeed, while liquid chromatography/mass spectrometry (LC/MS) studies of paired helical filament (PHF) tau revealed monophosphorylated peptides containing pT217 alone, pT212 was only found in peptides that also contained phosphorylation of S214 or T217 14 .…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…The assay relies on the high affinity and specificity of the PT3 mAb, which recognizes tau phosphorylated at threonine residues 212 and 217 22 . Phosphorylation of amino acid 217 is the minimally required epitope, yet phosphorylation of amino acid 212 enhances binding, and thus the recognition is termed “p217+tau.” As described for the CSF p217+tau assay, measurement of species containing both p212 and p217 may yield additional diagnostic relevance than measurement of just one of these residues 19 . Indeed, while liquid chromatography/mass spectrometry (LC/MS) studies of paired helical filament (PHF) tau revealed monophosphorylated peptides containing pT217 alone, pT212 was only found in peptides that also contained phosphorylation of S214 or T217 14 .…”
Section: Discussionmentioning
confidence: 99%
“…Predominantly observed species are comprised of N‐terminal, mid‐region, and select microtubule binding region (MTBR) epitopes, and additional major cleavage sites are likely in the region from aa 70‐120 and at ~aa 224 15,26,34,35,36 . Fractionation of CSF prior to assay has shown that CSF p217+tau is also entirely of fragmented nature, lacking C‐terminus and potentially also cleaved between aa7‐119 19 . Here we show, by comparing the p217+tau “short” and p217+tau “long” assay results, that plasma p217+tau may present a similar level of fragmentation in the aa 7‐119 region as in CSF.…”
Section: Discussionmentioning
confidence: 99%
“…More recently a high sensitivity Simoa assay has been developed using a capture antibody (pT3) that was raised against tau in paired helical filaments (PHF) of AD brain [12,13]. The core requirement for this antibody binding is phosphorylation at aa217 (p217) with enhanced binding when other nearby phosphorylated sites are present, predominantly at aa212 [12].…”
Section: Introductionmentioning
confidence: 99%
“…We then used an immunoassay which allows the quantification of tau phosphorylated at threonine 217 with or without adjacent phospho-epitopes (“p217 + tau” [ 12 ] (see also Supplementary Methods, online resource). P217 + tau also showed an age-dependent increase and reached a plateau, although at 14- to 16-fold higher levels compared to 1.5-month-old APPPS1 tg animals (Fig.…”
mentioning
confidence: 99%